RESPONSE OF TOMATO GROWTH TO FOLIAR AND SOIL APPLIED NITROGEN ALONE OR WITH POTASSIUM AND PHOSPORUS. 1) GROWTH PARAMETERS AND YIELD - Abdulkareem, M.A.; Ansari, A; Mehdi, S.A. (Emirates Journal of Food and Agriculture, 1997)
Please see the scanned pdf version in full text